Wants upon a time senior citizens' individual and social uses of media and the existence of a rural-urban media divide - Magtibay, Helene Grace D. (2012)
"There is a scarce of studies regarding the individual and social uses of media. Quite marked is the lack of studies regarding senior citizen's media viewing attitudes, preferences, and bahavior. Even the existence of an urban-rural media divide in the Philippine setting wasn't fully established yet. Hence, this study aimed to looking into the individual and social uses of different forms of media and the existence of a rural-urban media divide. Using both survey and focus interviews as research methods, data necessary in the fulfillment of this study were obtained from senior citizens with different backgrounds and with different geographic locations. A total of 200 senior citizens, 100 from Metro Manila and 100 from San Pascual, Batangas, and Lopez, Quezon were interviewed for this study. Findings of the study revealed that individual uses of media are categorized into three mainly 1) surveillance, 2) diversion, and 3) personal identity. On the other hand, social use of media is mainly to build personal relationships. The study also found that senior citizens are most exposed to the traditional forms of media rather than the new media. Out of the three conventional media forms, televisions is the medium they are most exposed to. It is also the respondents' most preferred medium. Furthermore, rural-urban divide is found to be non-existent in Metro Manila, and the provinces of Batangas and Quezon. This study could shed more light on the media consumption of the elderly. It can also be used by business and media industries whose target markets are senior citizens."